A pluriatividade como estratégia de reprodução da agricultura familiar no município de Caçapava do Sul - RS: um estudo de caso em cinco comunidades - Silva, Maria do Carmo da (2010)
This study beyond describing the strategies used in a form of production that combines family, land and labor, also searched to understand the issue of multiactivity consists in agricultural and non-agricultural activities carried out and developed by family farm and its members. The problems faced by family farmers, particularly farmers in the municipality of Caçapava do Sul concerns to income generation and new occupations once the process of low value of their products is historical. In this sense, the study proposes to understand and analyze the alternative strategies adopted by family production units that enables the creation of jobs and income for rural households, in a way to ensure their social and economic reproduction in the present situation, particularly in the borough of Caçapava do Sul, Rio Grande do Sul. Also to know the diversity of approaches adopted, and verify if multi-activity is a resource for work and income generation in the production units. The field work was carried out in the years 2009 and 2010 in the following communities: Vila Progresso, Rincão de Lourdes, Rincão da Salete, Coxilha de São José and Santa Barbinha, where was applied 50 (fifty) questionnaires and done 23 (twenty-three) interviews with producers distributed among the five communities, includes the interviews with technicians, rural associations presidents from the reported communities. The most outstanding features of the research in rural communities settle down on the few human and technical resources, in the pursuit of maximizing their potential productive: land shortage, simple labor and equipment, and in the lack of any planning.